2020
DOI: 10.1177/1094670520929095
|View full text |Cite
|
Sign up to set email alerts
|

The Smart Home: How Consumers Craft New Service Networks by Combining Heterogeneous Smart Domestic Products

Abstract: Service research suggests homes are becoming increasingly connected as consumers automate and personalize new forms of service provision. Yet, large-scale empirical evidence on how and why consumers automate smart domestic products (SDPs) is lacking. To address this knowledge gap, we analyze 13,905 consumer-crafted, automated combinations of SDPs, totaling 1,144,094 installations, across 253 separate service providers on the web service IFTTT.com . An exploratory network analysis examines the topology of the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 89 publications
0
19
0
Order By: Relevance
“…and Local Environment, each of which achieved especially high co-citation scores relative to their overall citations. The long-tailed nature of both the citation and co-citation distributions are similar to other social and technological networks (Albert and Barabási, 2002;Harvey et al, 2020). What stands out, however, is the recent rapid growth in this area of research in the past 5 years.…”
Section: Transdisciplinary Citation and Co-citation Network Analysismentioning
confidence: 55%
“…and Local Environment, each of which achieved especially high co-citation scores relative to their overall citations. The long-tailed nature of both the citation and co-citation distributions are similar to other social and technological networks (Albert and Barabási, 2002;Harvey et al, 2020). What stands out, however, is the recent rapid growth in this area of research in the past 5 years.…”
Section: Transdisciplinary Citation and Co-citation Network Analysismentioning
confidence: 55%
“…The smartness of service systems can vary considerably (Harvey et al 2020;Langley et al 2021;Pardo, Ivens, and Pagani 2020). Research by Henkens, Verleye, and Larivière (2021) concluded that smartness varies along four critical characteristics, which we apply to the smart watch example:…”
Section: Characteristics Of Smartness In Smart Service Systemsmentioning
confidence: 98%
“…As firms pursue smartness in various ways, different configurations of smartness emerge, which refer to managerial decisions on manipulating the four characteristics. Several studies have demonstrated how customers engage or disengage with smart products with varying levels of smartness (e.g., Chouk and Mani 2019;Harvey et al 2020;Henkens, Verleye, and Larivière 2021). Nonetheless, it has long been recognized that smart products are also reshaping how firms design service systems (Allmendinger and Lombreglia 2005;Porter and Heppelman 2014).…”
Section: Characteristics Of Smartness In Smart Service Systemsmentioning
confidence: 99%
See 2 more Smart Citations